BENEFITS OF PROPOLIS PERIODONTAL CHIP IN PERIODONTITIS-INDUCED MICE: CLINICAL PARAMETERS AND EXPRESSION OF INTERLEUKIN-1β (IL-1β) EVALUATION - KAREN, YULIA; NASUTION, RINI OCTAVIA; YUANDANI; ERVINA, IRMA; WULANDARI, PITU (International Journal of Applied Pharmaceutics, 2025)
Objective: Periodontitis is an infection of the tissues that support the teeth. This infection can cause serious damage to the gums, bone, cementum, and periodontal ligaments that hold the teeth in place. Scaling and root planing (SRP) is the standard non-surgical treatment for periodontal disease. This treatment involves removing plaque and calculus from the surfaces of the teeth and roots. Scaling and root planing are effective in eliminating harmful bacteria that cause infection, but they have limitations in reaching deep periodontal pockets and furcation areas. This may necessitate additional antimicrobial therapy to help control the infection. Propolis is a resinous substance produced by bees that has antibacterial and anti-inflammatory properties that have been shown to be beneficial in the treatment of various health conditions. Previous research has shown that 20% hydroalcoholic propolis extract as an additional therapy decreased probing depth score on periodontal pocket. Therefore, this study investigated the efficacy of propolis with lower concentration in reducing inflammation and Interleukin 1-β (IL-1β) levels. This research purposed to analysis the effectiveness of the application of periodontal propolis chip as adjuvant therapy in male Wistar rats on clinical parameters and Interleukin 1-β (IL-1β). Methods: An experimental laboratory study with a posttest control group design was conducted on 45 male Wistar rats induced with periodontitis using Porphyromonas gingivalis and ligated with silk. The rats were then divided into five treatment groups: placebo group (application of placebo periodontal propolis chip), positive control group (application of 2.5 mg chlorhexidine chip), treatment group 1 (application of 2.5% periodontal propolis chip), treatment group 2 (application of 5% periodontal propolis chip), and treatment group 3 (application of 10% periodontal propolis chip). Clinical parameter assessments (Gingival Index (GI), Bleeding on Probing (BoP), Pocket Depth (PD), Clinical Attachment Loss (CAL)) and IL-1β expression were performed on days 0, 3, and 7 after treatment in the rats. Results: The results of this study showed significant improvements and decreases in the clinical parameters GI, BoP, PD, and CAL. Examination of IL-1β expression also showed a significant statistical decrease (p<0.05). Conclusion: The application of a periodontal propolis chip can significantly improve GI, BoP, PD, and CAL and reduce IL-1β expression